Psychosocial Variables in Coronary Heart Disease - o’g’li, Raupov Abdurahmon Ortiq (American Journal of Biomedicine and Pharmacy, 2025)
The study of the connection between psychosocial variables and the progression of coronary heart disease (CHD) is the focus of this article. Patients with coronary artery disease are examined for social isolation, anxiety, and depression. the necessity of determining the psychological aspects that patients with coronary artery disease have in order to address them and enhance their quality of life and prognosis.